2017
DOI: 10.1111/bcpt.12744
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic Exposure in a Cohort of Adults Aged 80 years and Over

Abstract: Anticholinergics are frequently prescribed for older adults and can lead to adverse drug events. The novel MARANTE (Muscarinic Acetylcholinergic Receptor ANTagonist Exposure) scale measures the anticholinergic exposure by incorporating potency and dosages of each medication into its calculations. The aims were to assess prevalence and intensity of the anticholinergic exposure in a longitudinal cohort study of community‐dwelling patients aged 80 years and over (n = 503) and to study the impact on mortality and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…This discrepancy may result from the great heterogeneity of the studies included in the literature reviews, whether due to the characteristics of the study (delirium is rarely the primary objective of the study), the study population (number of patients included, settings, age) or the scale used, the most commonly used scales being ACB and ADS 16,24,26,28 . According the litterature, only one study has analyzed modi ed ADS 22 and two other have evaluated MARANTE scale 14,30 , which make it di cult to compare. In a recent study comparing 16 anticholinergic burden scales, Anticholinergic Cognitive load scale and ADS were considered to be the scales with the best inter-score agreement, with an inter-score correlation coe cient of 0.82.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may result from the great heterogeneity of the studies included in the literature reviews, whether due to the characteristics of the study (delirium is rarely the primary objective of the study), the study population (number of patients included, settings, age) or the scale used, the most commonly used scales being ACB and ADS 16,24,26,28 . According the litterature, only one study has analyzed modi ed ADS 22 and two other have evaluated MARANTE scale 14,30 , which make it di cult to compare. In a recent study comparing 16 anticholinergic burden scales, Anticholinergic Cognitive load scale and ADS were considered to be the scales with the best inter-score agreement, with an inter-score correlation coe cient of 0.82.…”
Section: Discussionmentioning
confidence: 99%
“…30 Furthermore, while we used the DBI to calculate the anticholinergic/sedative load, other tools have been developed, among those, one that shows promising results. 31,32 Finally while the feasibility, acceptability and potential effectiveness of the intervention appears high, the cost-effectiveness and implementation of medication recommendations and long-term medication changes in combination with relevant patient outcomes, like geriatric outcomes (e.g. fall risk, frailty and cognitive function) and adverse events (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Fox 2011 classed "low" exposure as ACBS one or more and "high" as ACBS two or more. Wauters et al (2017). These measures were: Clinician Rated Anticholinergic Scale (CrAS); Chew; Duran's list; MARANTE.…”
Section: Drug Burden Index-anticholinergic Component (Dbi (Antichol) )mentioning
confidence: 99%
“…Agar et al (2010) stated "Log-rank data showed no evidence that survival differed significantly between the three groups," however, no quantitative data were provided. Significant associations between ACB and mortality were produced by Gutieŕrez-Valencia et al (2017) [Duran's=1, OR 1.69 (95%CI 1.02-2.82) and Wauters et al (2017) (MARANTE "high" ≥2: HR 2.20 (95%CI 1.03-4.67)].…”
Section: Drug Burden Index-anticholinergic Component (Dbi (Antichol) )mentioning
confidence: 99%